Psoriasis: An Immunogenetic Perspective - Kocaaga, Ayca; Kocaaga, Mustafa (Global Medical Genetics, 2022)
Psoriasis is an erythematous-squamous dermatosis with a polygenic inheritance history. Both environmental and genetic factors play a role in the etiology of the disease. Over the past two decades, numerous linkage analyzes and genome-wide association studies have been conducted to investigate the role of genetic variation in disease pathogenesis and progression. To date, >70 psoriasis susceptibility loci have been identified, including HLA-Cw6, IL12B, IL23R, and LCE3B/3C. Some genetic markers are used in clinical diagnosis, prognosis, treatment, and personalized new drug development that can further explain the pathogenesis of psoriasis. This review summarizes the immunological mechanisms involved in the etiopathogenesis of psoriasis and recent advances in susceptibility genes and highlights new potential targets for therapeutic intervention.
Keywords: autoimmune; genome-wide association study; immunogenetics; psoriasis